Composition of Three Zingiberaceae Essential Oils and Their Efficacy Against the Survivability of Cocoa Pod Borer, Conopomorpha cramerella (Snellen) Eggs (Journal of the Bangladesh Agricultural University, 2024)
The use of botanical extracts derived from potential plants is promising due to their target-specific, biodegradable, and can be implemented in insect management programs. This study was conducted to observe the potential of three Zingiberaceae essential oils; Lesser galanga, Alpinia galanga, Turmeric, Curcuma longa; and ginger, Zingiber officinale against the Cocoa pod borer, Conopomorpha cramerella (Lepidoptera: Gracillariidae) - the most devastating pest of cocoa in the Southeast Asia region. Bioassay on the C. cramerella eggs were performed using four different concentrations of EOs at 100, 200, 400, and 800 ppm. It is found that the A. galanga performed as the best EOs that can disrupt egg hatchability (0.025b ± 0.158), where only 0.03 eggs hatched and significantly different (p